Pengaruh Penerapan Sistem E-Filing, Kesadaran Pelaporan Pajak dan Pemahaman Pajak Terhadap Kepatuhan Wajib Pajak (Studi Kasus Wajib Pajak Orang Pribadi di KPP Pratama Blitar) - Devi Kartikasari; Noor Shodiq Askandar; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study was to learn more about the implementation of an e-filing system, tax reporting awareness, tax comprehension, and taxpayer compliance. The research was quantitative. The population of the study is made up of individual taxpayers registered at the KPP Pratama Blitar. Purposive sampling was used in this study. With a total sample of 107 respondents, the slovin formula was used to calculate sampling. Furthermore, the data analysis technique employed multiple linear regression. According to the findings of the study, the implementation of an e-filing system, tax reporting awareness, and tax comprehension all had a positive effect on taxpayer compliance.Keywords: implementation of an e-filing system, taxpayers reporting awareness, tax comprehension, taxpayer compliance